Building the foundations for measuring learning gain in higher education: a conceptual framework and measurement instrument. Issue 1 (1st January 2018) - Vermunt, Jan D.; Ilie, Sonia; Vignoles, Anna
ABSTRACT: In this paper, we set out the first step towards the measurement of learning gain in higher education by putting forward a conceptual framework for understanding learning gain that is relevant across disciplines. We then introduce the operationalisation of this conceptual framework into a new set of measurement tools. With the use of data from a large-scale survey of 11 English universities and over 4, 500 students, we test the reliability and validity of the measurement instrument empirically. We find support in the data for the reliability of most of the measurement scales we put forward, as well as for the validity of the conceptual framework. Based on these results, we reflect on the conceptual framework and associated measurement tools in the context of at-scale deployment and the potential implications for policy and practice in higher education.